On the problems of reconstructing pre-hellenistic israelite (palestinian) history - Lemche, Niels Peter (The journal of Hebrew scriptures, 2001)
The biblical picture of ancient Israel does not fit in, but is contrary to any image of ancient Palestinian society that can be established on the basis of ancient sources from Palestine or referring to Palestine. There is no way this image in the Bible can be reconciled with the historical past of the region. And if this is the case, we should give up the hope that we can reconstruct pre-Hellenistic history on the basis of the Old Testament. It is simply an invented history with only a few referents to things that really happened or existed. From an historian's point of view, ancient Israel is a monstrous creature. It is something sprung out of the fantasy of biblical historiographers and their modern paraphrasers, i.e., the historical-critical scholars of the last two hundred years.